PENGARUH PUPUK ORGANIK CAIR UNITAS SUPER ASAL Chromolaena Odorata TERHADAP PERTUMBUHAN DAN HASIL PADI HITAM (Oryza sativa L.) - Jamilah Munir; Beben Kurniawan; Zahanis Zahanis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The aim of this research was to know the influence of concentration and interval of Liquid organic manure (LOM) Unitas Super (US) form Chromolaena odorata on growth and yield of black rice (Oryza sativa L.). The experiment was conducted from October 2016 to March 2017 in Lubuk Minturun Urban Village, Koto Tangah Sub-district, Padang. The experiments were arranged in Completely Randomized Design, with 6 doses of POC Unitas Super (US) (v/v) with water, ie; 0 ml L-1 (F1); 50 ml L-1, 1 time a week (F2), 50 ml L-1, 1 time 2 weeks (F3), 100 ml L-1, a weekly (F4), 100 ml L-1, 1 time every 2 weeks (F5); 150 ml L-1 POC US, 1 time every 3 weeks (F6), and 3 replications. The data obtained were analyzed using analysis of variance (ANOVA) 5% real level. If the treatment had a significant effect, it was continued with LSD test of 5% real level. Parameters observed include; Plant height, the maximum number of tillers and productive, flowering age, harvest, panicle length, the number of grains per panicle, weight of 1000 seeds, the weight of dry grain per hectare, percentage of empty grain and harvest index. The experimental results proved that there was an influence of LOM Unitas Super treatments on maximum tillers, empty grain, panicle length and dry grain harvest, and some other parameters were not significance. The conclusion was the giving of 50 ml L-1 POC Unitas Super given every week is the best treatment. The highest rice yield reached 6.79 tons ha-1 dry milled grain, with harvest index reached 0.49.